The Frequency of Using Herbal Medicines Among Patients With Hypertension in Kerman, Iran, 2012-2013. (July 2015) - Tajadini, Haleh; Divsalar, Kouros; Mehrabani, Mitra; Haghdoost, Ali Akbar; Esmaili, Zahra; Shadkam, Mitra; Moradi, Mehdi
Introduction . The use of medicinal plants has dramatically increased in recent years. Given the increasing rate of hypertension and medical plants usage by these patients and considering drug interactions due to concomitant use with drugs, the present study aims to evaluate the rate of medicinal plants usage in hypertensive patients. Methods . This is a cross-sectional study (descriptive–analytical) in which 650 hypertensive patients referring to the subspecialty clinic of Kerman were questioned about medicinal plants usage by a medicinal plants questionnaire. Among these patients, there were 612 who consented to participate. After the variables were described, the data were finally analyzed using Stata 12. Results . The average age of those using these drugs in the past year was 58.8 ± 10 years. Of the total number of participants using medicinal plants, there were 58 males (23.5%) and 122 females (33.4%). There were 129 participants (72.5%) using medicinal plants through self-administration, 17 participants (9.5%) on experienced users' advice, 16 participants (9%) as administered by herbalists, and 11 participants (6%) as administered by doctors. However, the most important resources for using a drug that prevents hypertension were family and friends (74 participants; 41.5%) and doctors (13 participants; 7.3%). According to the results, there was no significant difference between the level of education and medicinal plants usage ( P = .95); however, there was a significant difference between gender and medicinal plants usage ( P = .009). Discussion . According to the results indicating the relatively high prevalence of medicinal plants usage and their arbitrary use by hypertensive patients without consulting a specialist, it seems necessary to plan for more effective and secure public education and train people to provide herbal drug services for various diseases with hypertension being the most common one.